1991
DOI: 10.1007/bf01993121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloroquine on isolated mast cells

Abstract: Chloroquine liberated a relatively low amount of histamine from isolated rat mast cells. In a dose-dependent way, this drug inhibited histamine liberation from mast cells stimulated with compound 48/80, A23187, concanavalin A plus phosphatidylserine (Con A + PS) and abolished histamine liberation induced by exaprolol. The degranulation was decreased in cells stimulated with 48/80, Con A + PS and exaprolol. Chloroquine significantly inhibited the formation of thromboxane B2 in mast cells stimulated with 48/80, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The residual CQ-induced scratching behavior seen in mutant animals is likely due to an indirect effect on skin sensory nerves. Both our behavioral data from SASH mice and complete elimination of CQ-sensitive neurons in Mrgpr-clusterΔ −/− DRG support this notion and suggest that the residual CQ-induced response in Mrgpr-clusterΔ −/− mice results from degranulation of skin mast cells caused by the drug, a phenomenon observed in previous studies (Green and Lim, 1989; Nosal et al, 1991). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The residual CQ-induced scratching behavior seen in mutant animals is likely due to an indirect effect on skin sensory nerves. Both our behavioral data from SASH mice and complete elimination of CQ-sensitive neurons in Mrgpr-clusterΔ −/− DRG support this notion and suggest that the residual CQ-induced response in Mrgpr-clusterΔ −/− mice results from degranulation of skin mast cells caused by the drug, a phenomenon observed in previous studies (Green and Lim, 1989; Nosal et al, 1991). …”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have indicated that CQ can cause mast cell degranulation (Green and Lim, 1989; Nosal et al, 1991). To determine if this effect on mast cells contributes to CQ-evoked scratching behavior, we repeated the experiment on SASH mice, which lack mast cells due to a chromosomal inversion in the regulatory element of the Kit gene (Yamazaki et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It also directly activates TRPV4 channels . Hydroxychloroquine on the other hand, activates Mas‐related G‐protein coupled receptors, MrgprA3 and TRPA1 channels, and is considered to represent a model of “histamine‐independent” itch, but chloroquine also causes a release of classical mediators and arachidonic acid derived lipids from mast cells …”
Section: Resultsmentioning
confidence: 99%
“…Sensory neurons may thus not be the only source of NO following intradermal CQ injection. CQ also induces mast cell degranulation, (64, 65) releasing mediators that interact with afferent nerve fibers in the skin.…”
Section: Discussionmentioning
confidence: 99%